Weapons of mass destruction and terrorism - Forest, James J.F (McGraw Hill, 2013)
In WEAPONS OF MASS DESTRUCTION AND TERRORISM, 2/e, Dr. James Forest and Brigadier General (Retired) Russell Howard have collected original and previously published seminal articles and essays by scientists, academics, government officials, and members of the nation's security and intelligence communities. The editors and several of the authors write from practical field experience in nonproliferation and counterterrorism efforts. Others have had significant responsibility for developing government policies to address the threat of weapons of mass destruction and terrorism. The contributors include many significant names in the field including Bruce Hoffman, Ashton Carter, William Perry, Brian Jenkins, Jonathan Tucker, Charles Ferguson, David Albright, Gary Ackerman, and Gregory Koblentz. Unit I of the book introduces key terms and addresses important strategic and policy debates. Authors explain how the new forms of terrorism affect the post-9/11 security environment and how weapons of mass destruction could give terrorists short-term, asymmetric attack advantages over conventional military forces. Unit II offers detailed accounts of the characteristics, availability, and dangers of specific types of WMD, along with five case studies that associate theory with practice-an important feature of this volume. Unit III is focused on key dimensions of the WMD threat to critical infrastructure. Unit IV deals with past, present, and future national and international responses to-and defenses against-the threat of WMD terrorism. And in the final section of the volume, authors provide several analytical frameworks for predicting future WMD threats, and draw from historical events to identify lessons and strategies for the future. Appendices include U.S. national strategy documents on countering terrorism and standards for controlling WMD materials and technologies.